2001
DOI: 10.1182/blood.v98.6.1654
|View full text |Cite
|
Sign up to set email alerts
|

Partial amino acid sequence of purified von Willebrand factor–cleaving protease

Abstract: von Willebrand factor-cleaving protease (vWF-cp) is responsible for the continuous degradation of plasma vWF multimers released from endothelial cells. It is deficient in patients with thrombotic thrombocytopenic purpura, who show unusually large vWF multimers in plasma. Purified vWF-cp may be useful for replacement in these patients, who are now treated by plasma therapy. In this study, vWF-cp was purified from normal human plasma by affinity chromatography on the IgG fraction from a patient with autoantibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
254
2
9

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(269 citation statements)
references
References 39 publications
4
254
2
9
Order By: Relevance
“…7), confirming that domains C-terminal to the spacer domain are not required for proteolytic activity in vitro. If full-length recombinant and plasma ADAMTS13 (Ϸ170 kDa) have similar specific activity, the results suggest that the plasma concentration of active ADAMTS13 is Ϸ1.6 g/ml, which is similar to the value of 1 g/ml based upon the recovery of ADAMTS13 during purification from plasma (11). DISCUSSION The complex modular structure of many ADAMTS proteases is highly conserved among vertebrates, suggesting that their noncatalytic domains perform specific selectable functions.…”
Section: Fig 5 Adamts13 Variants Expressed In Cos-7 Cellssupporting
confidence: 57%
See 1 more Smart Citation
“…7), confirming that domains C-terminal to the spacer domain are not required for proteolytic activity in vitro. If full-length recombinant and plasma ADAMTS13 (Ϸ170 kDa) have similar specific activity, the results suggest that the plasma concentration of active ADAMTS13 is Ϸ1.6 g/ml, which is similar to the value of 1 g/ml based upon the recovery of ADAMTS13 during purification from plasma (11). DISCUSSION The complex modular structure of many ADAMTS proteases is highly conserved among vertebrates, suggesting that their noncatalytic domains perform specific selectable functions.…”
Section: Fig 5 Adamts13 Variants Expressed In Cos-7 Cellssupporting
confidence: 57%
“…The VWF-cleaving protease was recently purified and identified as a new member of the ADAMTS family of metalloproteases (10,11), so named for the combination of a disintegrin-like and metalloprotease (reprolysin type), with thrombospondin type 1 motifs (12). The primary structure of the ADAMTS13 precursor was determined by cDNA cloning (13,14) and by positional cloning in families with inherited AD-AMTS13 deficiency (15).…”
mentioning
confidence: 99%
“…15,16 Most recently, this enzyme has been purified as a single-chain glycoprotein with a molecular mass of ෂ150 kDa by two different groups of investigators. 17,18 Northern blotting based on the N-terminal amino acid sequence of this purified enzyme revealed that the full-length (4.6 kb) mRNA is only expressed in liver, and cDNA sequencing identified this enzyme as a new member of the metalloproteases belonging to the ADAMTS (a disintegrin-like domain, and metalloproteinase, with thrombospondin type-1 motif) family, designated ADAMTS13. [18][19][20] The deduced amino acid residue number of this enzyme is 1427, and its gene is located on chromosome 9q34.…”
Section: And Jones Et Almentioning
confidence: 99%
“…The specific protease activity of recombinant mADAMTS13 (3 U/mlC8 nmol/l ¼ 375 U/nmol) was similar to the presumed specific activity of human plasma ADAMTS13 (1 U/mlC5 nmol/l ¼ 200 U/nmol, assuming plasma ADAMTS13 level ¼ 1 mg/ml, or 5 nmol/ l). 22 These estimates need to be confirmed in the future by direct analysis of purified proteins. We also determined the ADAMTS13 activity level in the heparin-anticoagulated plasma of FVB/N mice by using the same hVWF substrate and found that the mean (7s.d.)…”
Section: Cloning Of Mouse Full-length Adamts13mentioning
confidence: 98%